Medication Errors in Adolescents Using Asthma Controller Medications - Henry Clark Pharm D; Delesha Carpenter PhD; Kathleen Walsh MD; Scott A. Davis PhD; Nacire Garcia MS; Betsy Sleath PhD (SAGE Publishing, 2020)
The purpose of this study was to describe the number and types of errors that adolescents and caregivers report making when using asthma controller medications. A total of 319 adolescents ages 11 to 17 with persistent asthma and their caregivers participated in this cross-sectional study. Adolescent and caregiver reports of asthma medication use were compared to the prescribed directions in the medical record. An error was defined as discrepancies between reported use and the prescribed directions. About 38% of adolescents reported 1 error in using asthma controller medications, 16% reported 2 errors, and 5% reported 3 or more errors. About 42% of caregivers reported 1 error in adolescents using asthma controller medications, 14% reported 2 errors, while 6% reported 3 or more errors. The type of error most frequently reported by both was not taking the medication at all. Providers should ask open-ended questions of adolescents with asthma during visits so they can detect and educate families on how to overcome errors in taking controller medication use.